Digital Ecosystems: The Adtech Tax and Content Quality - Anna D'Annunzio; Antonio Russo; Shiva Shekhar (CESifo GmbH, 2024)
The adtech industry plays a key role in facilitating connections between digital publishers and advertisers. This paper studies the impact of vertical integration between an intermediary and a major publisher on the online advertising ecosystem and the provision of content. We find that vertical integration enables the intermediary to leverage exclusive access to data, leading to dominance in the intermediation market. As a result, the integrated intermediary is able to collect a larger ad-tech tax from independent publishers by shading its bid for impressions. This practice reduces investments in content by independent publishers, while the integrated publisher increases its investment. Therefore, the net effect of vertical integration on consumer welfare and total welfare can be positive or negative. We discuss potential policy interventions that restore the outcome as under vertical separation.
Keywords: D43; D62; L82; M37; 330; online advertising; intermediaries; vertical integration; adtech tax; content quality